Peptide Sharing Between Viruses and DLX Proteins: A Potential Cross-Reactivity Pathway to Neuropsychiatric Disorders - Lucchese, Guglielmo; Stahl, Benjamin (Frontiers in Neuroscience, 2018)
The present study seeks to determine potential associations between viral infections and neuropsychiatric diseases. To address this issue, we investigated the peptide commonalities between viruses that have been related to psychiatric and neurological disorders – such as rubella, human immunodeficiency virus, and herpesviruses – and human distal-less homeobox (DLX) proteins expressed in developing brain – namely, DLX1, DLX2, DLX5, and DLX6. Peptide matching analyses revealed a high degree of pentapeptide sharing. From an immunological perspective, this overlap is relevant because pentapeptides are endowed with immunogenicity and antigenicity – that is, they are immune determinants. Moreover, infection-induced immune cross-reactions might have functional, spatial and temporal implications related to the functions and expression patterns of DLX1 and DLX5 in the fetal and adult human brain. In sum, our data support the hypothesis that viral infections may be linked to neuropsychiatric diseases through autoimmune cross-reactions caused by molecular mimicry between viral proteins and brain-specific DLX self-antigens.